A Case of Depressed Skull Fracture of the Inner Table Alone - Eom, Ki Seong (Korean J Neurotrauma, 2021)
A depressed skull fracture (DSF) is comminuted fractures in which the broken bones displace inward due to a blunt head trauma, such as when the broken outer table is located below the normal anatomical position of the inner table. The author presents an extremely rare case of a 38-year-old man with a DSF that affected only the inner table. In the literature, only 2 cases of DSF involving only the inner table have been reported, and the underlying mechanism remains unclear. The author believes that this phenomenon was not enough for the impact force to depress the outer table, but the tensile stress was sufficient to depress the relatively thin and weak inner table.